2016
DOI: 10.2217/fon.15.351
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Enzalutamide on the Treatment of Prostate Cancer

Abstract: The field of prostate cancer has witnessed incredible progress in the last decade, owing to the approval of multiple survival-prolonging treatments for metastatic castration-resistant prostate cancer (mCRPC). Enzalutamide is a nonsteroidal androgen receptor inhibitor that targets multiple steps in the androgen receptor signaling axis. It has been approved for the treatment of mCRPC both in the postdocetaxel and in the chemotherapy-naive settings. We summarize the milestones in the development of enzalutamide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 15 According to previous studies, 16 we deduced that bicalutamide resistance was attributable to AR-Vs. Moreover, various clinical studies found that abiraterone and enzalutamide had no satisfactory long-term therapeutic effect in the mCRPC patients with AR-Vs. 17 These findings could explain the high-level PSA of the patient, especially for the late stage of treatment. It was also notable that the PI3K-AKT-mTOR signaling pathway was altered in almost 100% of advanced-stage PCas.…”
Section: Discussionmentioning
confidence: 93%
“… 15 According to previous studies, 16 we deduced that bicalutamide resistance was attributable to AR-Vs. Moreover, various clinical studies found that abiraterone and enzalutamide had no satisfactory long-term therapeutic effect in the mCRPC patients with AR-Vs. 17 These findings could explain the high-level PSA of the patient, especially for the late stage of treatment. It was also notable that the PI3K-AKT-mTOR signaling pathway was altered in almost 100% of advanced-stage PCas.…”
Section: Discussionmentioning
confidence: 93%
“…A phase II study with apalutamide demonstrated durable activity in non-mCRPC, pre- and post-abiraterone acetate, and prednisone mCRPC arms with a median PSA level at week 12 decreasing to 85%, 88%, and 22%, respectively . Apalutamide in phase III trials of CRPC achieved median metastasis-free survival of 40 months compared with 16 months for the placebo . A common side effect of apalutamide is skin rash, which can be attributed to the cyano pyrimidine moiety, which is capable of attaching to cysteine residues in proteins through a reversible covalent bond …”
Section: Clinical Development Of Second-generation Ar Antagonistsmentioning
confidence: 99%
“…187 Apalutamide in phase III trials of CRPC achieved median metastasis-free survival of 40 months compared with 16 months for the placebo. 188 A common side effect of apalutamide is skin rash, which can be attributed to the cyano pyrimidine moiety, which is capable of attaching to cysteine residues in proteins through a reversible covalent bond. 189 JNJ-63576253 ( 110) is a clinical stage second-generation AR antagonist capable of overcoming a subset of enzalutamide and apalutamide resistance.…”
Section: Relation Between Agonist and Antagonistmentioning
confidence: 99%
“…Another phase II trial, evaluating new anti androgen receptor which is enzalutamide. Enzalutamide is antiandrogen that inhibit androgen receptor signalling pathway which will prevent transcription of androgen responsives gene (Nadal & Bellmunt, 2016). In this study 118 patients were received enzalutamide 160mg once per day until disease progression.…”
Section: Androgen Receptormentioning
confidence: 99%